Reductive dechlorination under acidic condition - Jiang, Xie (2014)
Chlorophenols with their toxicity, persistence and detrimental effects on the environment raise great concerns. Biological treatment seems to be the most economical way when dealing with wastewater containing these chlorinated compounds. Anaerobic dechlorination of chlorophenols has been extensively investigated. Despite it being effective in degrading chlorophenols, the process suffers from instabilities during operation. The imbalanced growth kinetics between acidogens and methanogens, accumulation of fermentative products leading to acidification of the system and methanogens’ sensitivity to toxic compounds, like chlorophenols, make the whole process less stable and difficult to maintain. To solve the problem of process instability, acidogenic dechlorination of chlorophenols as pretreatment becomes a possible alternative. However, there are concerns still unaddressed such as: 1) To date, very few findings have been reported on acidogenic dechlorination process. Contradictory conclusions were drawn among different researchers; 2) Acidic condition is not the appropriate environment for the growth of chlororespirating bacteria; 3) The role of methanogens in dechlorination is arguable as different researchers reported contradictory findings. Excluding methanogens in the acidogenic environment for dechlorination is not conclusive in this case. In this project, the anaerobic sequencing batch reactor (anSBR) was acclimated and operated at pH 5.5. The reduction of pH followed the step-wise reduction manner at the rate of 0.5 per week. The acclimated acidic sludge demonstrated capability to dechlorinate 2-MCP, 2,4,6-TCP and PCP but this was limited to attacking ortho-chlorines only. Besides the long acclimation period (80 days) initially, the acclimated sludge was dechlorinated TCP and PCP without lag phase. When inhibited, caused by PCP overloading and extreme low pH (2.0), dechlorination was severely curtailed. It was found the inhibition was associated with methanogen’s activity curtailment, whereas acidogenesis still continued. The qPCR analysis of microbial communities revealed the Methanosarcinaceae family was the only group, which dropped sharply in terms of copy number. These results led to the hypothesis that methanogens participated in the dechlorination of chlorophenols under acidic condition. Specific inhibitors to methanogens and gram-positive bacteria were applied to investigate the roles of different groups of anaerobes in dechlorination. Both inhibitors affected dechlorination, with the methanogenic specific inhibitor (BES) inhibiting dechlorination of 2-MCP no matter which electrons were applied. The antibiotic of gram-positive bacteria (vancomycin) did inhibit dechlorination as well. In addition, more methane was produced in batches with dosage of vancomycin suggested that acetate was directed to methanogenesis from other pathways during the inhibition. The findings in this study implied a syntrophism was involved in dechlorination. Both methanogens and the acetate-oxidizing bacteria should be properly maintained in order to perform dechlorination of 2-MCP under acidic condition. The results found in this project implied it was not possible to exclude methanogens from the dechlorination process hence the instability issues associated with the conventional anaerobic dechlorination may not be solved by phase separation in the traditional sense. Community analysis of the sludge did suggest there were in fact limited phenotypes of methanogens, which could survive and participate in the dechlorination process. The system preferentially selected certain groups of methanogens, which demonstrated the ability to survive in the low pH environment. This project confirmed the notion the acidic reactor could dechlorinate chlorophenols but with the participation of methanogens and acetate-oxidizing bacteria. The process was therefore not strictly phase separated but was shown to be a viable treatment process for chlorophenols.